Beyond pathogens: the intriguing genetic legacy of endogenous retroviruses in host physiology - da Silva, Amanda Lopes; Guedes, Bruno Luiz Miranda; Santos, Samuel Nascimento; Correa, Giovanna Francisco; Nardy, Ariane; Nali, Luiz Henrique da Silva; Bachi, Andre Luis Lacerda; Romano, Camila Malta (Frontiers in Cellular and Infection Microbiology, 2024)
The notion that viruses played a crucial role in the evolution of life is not a new concept. However, more recent insights suggest that this perception might be even more expansive, highlighting the ongoing impact of viruses on host evolution. Endogenous retroviruses (ERVs) are considered genomic remnants of ancient viral infections acquired throughout vertebrate evolution. Their exogenous counterparts once infected the host’s germline cells, eventually leading to the permanent endogenization of their respective proviruses. The success of ERV colonization is evident so that it constitutes 8% of the human genome. Emerging genomic studies indicate that endogenous retroviruses are not merely remnants of past infections but rather play a corollary role, despite not fully understood, in host genetic regulation. This review presents some evidence supporting the crucial role of endogenous retroviruses in regulating host genetics. We explore the involvement of human ERVs (HERVs) in key physiological processes, from their precise and orchestrated activities during cellular differentiation and pluripotency to their contributions to aging and cellular senescence. Additionally, we discuss the costs associated with hosting a substantial amount of preserved viral genetic material.